2021
DOI: 10.3389/fgene.2021.717319
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a Tumor Microenvironment-Related Gene Signature in Hepatocellular Carcinoma Prognosis

Abstract: Background: Hepatocellular carcinoma (HCC) is a typical inflammatory-related malignant tumor with complex immune tolerance microenvironment and poor prognosis. In this study, we aimed to construct a novel immune-related gene signature for the prognosis of HCC patients, exploring tumor microenvironment (TME) cell infiltration characterization and potential mechanisms.Methods: A total of 364 HCC samples with follow-up information in the TCGA-LIHC dataset were analyzed for the training of the prognostic signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Previous studies have proven that NQO1, ETV4, BSG, and HMGA1 are highly expressed in HCC (Jin et al, 2019;Teng et al, 2019;Yang et al, 2021;Zheng et al, 2022). In addition, the upregulation of PBK, BIRC5, PLK1, and EZH2 was also validated in HCC tissues (Xiao et al, 2019;Yang et al, 2019;Tian et al, 2020;Huang et al, 2021;Lin et al, 2021;Peng et al, 2021). However, the…”
Section: Dap3 Was Upregulated In Hepatocellular Carcinoma Tissuesmentioning
confidence: 97%
“…Previous studies have proven that NQO1, ETV4, BSG, and HMGA1 are highly expressed in HCC (Jin et al, 2019;Teng et al, 2019;Yang et al, 2021;Zheng et al, 2022). In addition, the upregulation of PBK, BIRC5, PLK1, and EZH2 was also validated in HCC tissues (Xiao et al, 2019;Yang et al, 2019;Tian et al, 2020;Huang et al, 2021;Lin et al, 2021;Peng et al, 2021). However, the…”
Section: Dap3 Was Upregulated In Hepatocellular Carcinoma Tissuesmentioning
confidence: 97%
“…BIRC5 appears to be an independent, unfavorable prognostic biomarker in multiple types of tumors and has potential as a clinical target for future cancer therapies 30 . Moreover, BIRC5 has been shown to play a role in the construction of prognostic models for various types of LIHC [31][32][33] , suggesting its potential as a valuable biomarker in the clinical management of cancer. Studies indicated that MMPs are directly or indirectly involved in the regulation of mitochondrial oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…BIRC5 appeared to be an independent unfavorable prognostic biomarker in multiple types of tumors and had the potential as a clinical target for future cancer therapy (30). Moreover, BIRC5 had been demonstrated to play a role in constructing prognostic models for various types of LIHC (31)(32)(33), suggesting its potential as a valuable biomarker in the clinical management of cancer. Studies indicated that MMPs were able to be directly or indirectly involved in the regulation of mitochondrial oxidative stress.…”
Section: Discussionmentioning
confidence: 99%